PERAN LEMBAGA KEUANGAN BANK DAN LEMBAGA KEUANGAN BUKAN BANK DALAM MEMBERIKAN DISTRIBUSI KEADILAN BAGI MASYARAKAT - Jamal Wiwoho (Faculty of Law, Universitas Diponegoro, 2014)
Financial institutions is expected to provide justice for the distribution. Formulation of the problem that researchers ask is how the role of banks financial institutions and non-bank in providing public justice and the factors driving the increased role of banks and financial institutions non-bank in providing the distribution of public justice. The result of the research are 1). The role of financial institutions are: raise public funds; channelling funds society; transfer of assets; liquidity; allocation of income;. transaction. 2). Factors that encourage an increased role of financial institutions in providing the distribution of public justice, among others: increase amount of income of the middle class families and individuals with sufficient incomes, especially among the middle and have a portion of income for savings each year; rapid development of industry and technology.